Cost of debt for private firms revisited: voluntary audits as a reflection of risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa (International Review of Economics & Finance)
We examine the relation between voluntary audit and the cost of debt in private firms. We use a sample of 7420 small private firms operating in the period 2006-2022 that are not subject to mandatory audits. Firms self-select into voluntary audits because of the economic setting (e.g., ownership complexity, export, subsidiary status) or because firm fundamentals limit their access to financial debt. In the outcome analyses, we find that voluntary audits result in higher, rather than lower, interest rates with increases ranging from approximately 1.7 percentage points, but going higher depending on the exact specification. This effect is present regardless of the perceived audit quality (Big-4 vs. non-Big-4), consistent across auditor types. Audited firms’ earnings are less informative about future operating performance. Voluntary audits facilitate access to financial debt for high-risk firms. The price paid is reflected in higher interest rates for voluntary audits – firms with higher information/fundamental risk.

The Role of Stakeholders in CSR Reporting of Non-Listed Banks - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska (Accounting in Europe)
We investigate the role of stakeholders in the CSR reporting of non-listed savings banks in Germany. They are established by municipal trustees and serve clients in their distinct operating area. Reporting discretion under the Non-Financial Reporting Directive may lead to variation in CSR reporting due to differences in sustainability interests of banks’ stakeholders and CSR governance (e.g. existence of a CSR manager). We document that the CSR reports and specific CSR dimensions are intensely associated with the existence of strong CSR governance and to a lesser extent with the interests of municipal trustees and bank clients. However, the associations with these stakeholders are predominantly present in banks with strong CSR governance. Our findings inform policy discussions about detailed CSR disclosure requirements (e.g. the European Sustainability Reporting Standards) and extension of reporting scope to firms with regional orientation and absence of typical shareholders.

Neue Mikrodaten zu Unternehmensinsolvenzen in Deutschland: Die insol Datenbank - Rahali, Mahdi; Beyer, Bianca; Gassen, Joachim; Geschonke, Sebastian

COVID-19 insolvency moratoria, firm selection, and allocative efficiency - Rahali, Mahdi

Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

Brexit and European Corporate Bond Markets - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
We investigate the impact of Brexit on the corporate bond market by analyzing a comprehensive database covering corporate bond listings on European and UK trading venues. We find a significant shift in bond market activity, evidenced by a 49% increase in the number of bond listings in the EEA30 countries relative to the UK market after Brexit. Country-level analyses reveal a staggered effect on market activity, with predominantly international issuers adjusting their bond listings between the initially scheduled Brexit date and the final withdrawal date. At the issuer level, our findings indicate that the relative attractiveness of the EEA30 market has increased post-Brexit. Overall, these results suggest that the European capital market has successfully adapted to the loss of its largest financial center and exhibits a rising corporate bond market activity.

Are firms (getting) ready for the corporate sustainability reporting directive? - Kosi, Urska; Relard, Paula (Sustainability Nexus Forum)
The study examines whether the announcement and passing of the Corporate Sustainability Reporting Directive (CSRD) impacts the sustainability reporting of German firms. It sheds light on the interdependence of various actors, sectors and policy levels by examining how regulatory changes at the policy level affect the reporting practices of firms across multiple sectors. On the one hand, the scope of the CSRD is being extended, so that new firms falling within its scope may increase their voluntary sustainability reporting as part of the preparation process. On the other hand, the reporting requirements will be more stringent, so that firms currently under the mandate of the Non-Financial Reporting Directive (NFRD) may enhance their sustainability reporting disclosure practices in preparation for the CSRD. First, we find no increase in voluntary sustainability reporting by firms that are not under the scope of the NFRD but will be under the scope of the CSRD. Second, we find enhanced sustainability reporting practices by firms that are subject to the NFRD after the CSRD’s announcement and passing. This finding suggests that these firms begin to implement the new reporting requirements before the first reports are published in 2025. We illuminate the preparation for extensive reporting changes through sustainability reporting disclosure practices as an outcome of the preparation process. These changes may represent a high burden, particularly for firms with no previous experience of sustainability reporting.

Information Leaks and Voluntary Disclosure - Ebert, Michael; Schäfer, Ulrich; Schneider, Georg Thomas

Current developments in the European corporate bond market - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
This paper introduces a novel database on the European corporate bond market to analyze the role of transparency regulation and recent developments in bond markets. We use data from the European Securities and Markets Authority (ESMA) to build a comprehensive database covering daily corporate bond listing information in Europe starting in 2018. We then analyze the different market segments of the European bond market along four key areas: (i) time and cross-sectional trends in bond listings; (ii) composition of firms on the market; (iii) firms’ financial reporting transparency; (iv) bond contract terms. Furthermore, we discuss the impact of recent economic events on these key areas.
Keywords: Transparency regulation; Corporate bond; European market

CSR Reporting under the Non-Financial Reporting Directive: Evidence from Non-publicly Listed Firms - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska
We examine variation in mandatory CSR reporting practices based on a large sample of non-publicly listed savings banks in Germany. They do not have typical shareholders but rather are established by municipal trustees and can serve clients only in their distinct operating area. This setting permits us to identify demand for CSR information by their main stakeholder groups – municipal trustees and private and corporate clients. In this way, our analysis focuses on the double-materiality approach to CSR reporting. We find that demand for CSR information by supervisory board chairperson belonging to a left-wing or green party and the presence of more supervisory board members belonging to a left-wing or green party are associated with longer CSR reports and more disclosure on environmental, social, employee and human rights matters. In addition, competition for private clients and the sustainability orientation of corporate clients are associated with longer reports and more disclosure on environmental, employee and human rights matters. These findings suggest that savings banks’ CSR reports cater to their principal stakeholders’ demand for CSR information.
Keywords: Corporate social responsibility; Mandatory reporting; Non-publicly listed banks; Double materiality; Stakeholder groups; Political influence

Insolvency Process in Germany and the insol database: A Research Note - Ahlers, Theresa; Edossa, Fikir Worku; Kosi, Urska; Uckert, Mathias
This research note links the legal framework of the insolvency process of German firms to the information available in the newly-constructed insol database. In particular, the database contains information from documents published by German insolvency courts in period 2005- 2022. This research note first presents the insolvency process with steps and events of the process as determined by the Insolvency Law (InsO). Next, it classifies the documents to specific steps and events, and then presents their information content using textual analysis. Specifically, we identify target phrases via manual document checks and then create regular expressions for the target phrases. Classification of documents allows us to sketch most common paths that insolvent firms go through.
Keywords: insol database; insolvency process; Germany; court fillings

Does private firms’ disclosure affect public peers’ information environment? - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska

Forschung und Entwicklung: Kriterien für die Aktivierung in der Unternehmenspraxis - Blankenfeldt, Maximilian; Müller, Jens; Weinrich, Arndt (Intangibles - Immaterielle Werte)

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Debora; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that captures the complexity of countries’ corporate income tax systems faced by multinational corporations. It is based on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries for the year 2016, we find that the level of tax complexity varies considerably across countries, while tax code and framework complexity also vary within countries. From a global perspective, tax complexity is strongly driven by the complexity of both transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different correlation patterns. For example, tax framework complexity is negatively associated with countries’ governance, suggesting that strongly governed countries tend to have less complex tax frameworks, while tax code complexity is positively associated with the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associa-tions are very strong. We conclude that tax complexity represents a distinct country charac-teristic and propose the use of our TCI and its subindices in future research.

Eine ökonomische Einordnung des öffentlichen Country-by-Country Reporting in der EU - Hoppe, Thomas; Müller, Jens; Wittek, Katharina; Weinrich, Arndt (iStR)

Bankruptcies: A victim of the corona crisis? TRR 266 Accounting for Transparency. - Gassen, Joachim; Kosi, Urska (Bankruptcies: A victim of the corona crisis?)

Information Design in Coordination Games with Risk Dominant Equilibrium Selection - Ebert, Michael; Kadane, Joseph (Jay) B.; Simons, Dirk; Stecher, Jack Douglas

Do Country Risk Factors Attenuate the Effect of Tax Loss Incentives on Corporate Risk-Taking? - Osswald, Benjamin; Sureth-Sloane, Caren
This study investigates whether country risk factors, including political and fiscal budget risk, attenuate the effectiveness of tax policy tools that aim to encourage corporate risk-taking. Exploiting a cross-country panel, we predict and find that the effectiveness of loss offset rules and tax rate changes is fully attenuated for firms located in high-risk countries. We document the attenuating effect of country risk is more pronounced in high-tax countries or when countries increase their corporate tax rate. Additional tests around the U.S. federal budget crises from 2011 to 2013 indicate that temporarily heightened fiscal budget risk attenuates the effectiveness of loss offset rules even in countries with low political risk. We identify conditions (low political and low fiscal budget risk) under which targeted tax policy tools effectively stimulate risk-taking. This suggests that ensuring taxpayers receive tax refunds is important in times of economic crises with budgetary or political challenges.